DEVELOPMENT TENDENCY OF INVESTMENT LEGISLATION: INTERNATIONAL EXPERIENCE AND NATIONAL LEGISLATION - Dilboboyev Nozimbek Shavkat ugli (Scholar Express Journals, 2023)
Nowadays, relations with the investment sector are growing rapidly on a global scale. Investment relations are becoming so complex that it is connecting with almost all branches of law and becoming a separate field. At the same time, investment is also an economic category, which requires interdisciplinary research. This thesis analyzes the development trends of investment legislation at the international level and analyzes the views on the current situation and potential changes in comparison with the development trends of the national legal system
Keywords: Investment; Foreign Investment; Expropriation